ANALISIS PENGARUH TATA KELOLA, BELANJA MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN EMISI KARBON - Cecilia Rooschella; Virna Sulfitri (LPPM Universitas Ibnu Sina, 2023)
This study aims to analyze the effect of corporate governance, capital expenditure, profitability, and firm size on carbon emissions disclosure. Data was used from companies that operating in five sectors listed on Indonesia Stock Exchange, including the consumer non-cyclicals, basic materials, energy, industry, and infrastructure. This study collects secondary data which are reported their Annual Report and Sustanability Report from 2017-2021. Data analysis method used is multiple linear regression. The result of the study prove that corporate governance variable has a negative effect on carbon emissions disclosure. However, three other independent variables, namely capital expenditure, profitability and firm siza have positive effect on carbon emissions disclosure.